1996
DOI: 10.1152/ajpheart.1996.271.2.h528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparin on fibrinolytic activity and platelet function in vivo

Abstract: Heparin, a polyanionic glycosaminoglycan, is used routinely before the induction of cardiopulmonary bypass. Earlier observations in our laboratory suggested that the postoperative bleeding that occurs, despite neutralization of heparin with protamine, is secondary to hypothermia and dilutional anemia during bypass. An additional, potential mechanism for excessive bleeding following cardiopulmonary bypass is that heparin activates the fibrinolytic system, which may, in turn, adversely affect hemostasis. To unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…However, this decrease was significantly worse when conventional NHB circuits were utilized for CPB (Table 3). These alterations in hematological parameters are consistent with what has been observed by others [1,4,22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, this decrease was significantly worse when conventional NHB circuits were utilized for CPB (Table 3). These alterations in hematological parameters are consistent with what has been observed by others [1,4,22].…”
Section: Discussionsupporting
confidence: 93%
“…The conventional practice of using a nonthromboresistant extracorporeal circuit in cardiac surgery has been shown to induce a variety of hematological and inflammatory adverse events [1][2][3]. These effects are the result of the foreign surfaces of the cardiopulmonary bypass (CPB) circuit, high-dose heparin anticoagulation, systemic hypothermia, hemodilution, and the open perfusion bypass system that allows air to interface with blood as a foreign surface during surgery [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies have shown that heparin administration a), results in a rapid release of t-PA from its body sources, which may induce fibrinolysis [79], b) causes (in vitro) inhibition of platelet function in more than 30% of patients, thus leading to increased postoperative blood loss [80], c) has pro-activating properties on granulocytes and platelets [81], and finally d), heparin after its neutralization with protamine, is inducing an activation of the complement system, action which is correlated with postoperative pulmonary shunt fraction [82]. To avoid these adverse effects of heparin, some possible alternatives have been proposed.…”
Section: Methodology and Strategy For Management Of Lung Dysfunction mentioning
confidence: 99%
“…A previous study from our laboratory has documented that heparin produced a platelet dysfunction and fibrinolysis in patients before cardiopulmonary bypass surgery 25 . In another study from our laboratory infusion of heparin into the baboon induced fibrinolytic activity, 100 units per kg of heparin produced a heparin level of 7.8 units per mL and a plasmin level of 72.7 units per liter 50 minutes following the infusion into baboons 26 …”
Section: Discussionmentioning
confidence: 82%